THE TREATMENT OF ACUTE ANGLE CLOSURE WITH HISTORY OF PSYCHOTROPIC AGENTS : A CASE REPORT: Poster Presentation - Case Report - Resident - Rafika; Subsp GL, Dr. dr. Fidalia Sp.M (K); Sari Sp.M (K) Subsp GL, Dr. dr. Prima Maya (Majalah Oftalmologi Indonesia, 2023)
Introduction : Psychotropic agents may precipitate Acute Angle Closure (AAC) either by inducing pupil block via adrenergic or anticholinergic mechanisms, or via an idiosyncratic non-pupillary block mechanism. This is a serious condition that can diminished aquous humor (AH) outflow and increased intraocular pressure Case Illustration : A 60-year-old female complained of a sudden onset of a severe painful red eye on the right eye (RE)2 weeks ago and there was an IOP elevation. Anti-glaucoma medications were given with no succcess. The patient regularly consumed psychotropic drugs Trihexyphenidyl, Risperidone, and Chlopromazine since 2005 and Escitalopram since 2 years ago Discussion : Several classes of centrally acting drugs, including antidepressants such as selective serotonin receptor inhibitors (SSRIs) and antipsychotics have been implicated in precipitate AAC in individuals with pre-existing narrow angels. Rapid lowering of the IOP including medical treatment and relieved relative pupillary block with laser peripheral iridotomy (LPI) is an important initial step in treating AAC. Because the media is not clear due to corneal edema, trabeculectomy + 5 Fluorouracil can be considered for IOP control to prevent further damage. Conclusion : Trabeculectomy + 5 FU procedures may be a valuable and effective option in cases where LPI is too risky due to unclear visualization because of corneal edema. Trabeculectomy has been shown to effectively reduce IOP. Closed monitoring is necessary to assess ocular side effects due to the use of psychotropic agents